PENENTUAN BOBOT KEPENTINGAN DECISION MAKER DALAM GROUP DECISION MAKING - Dian Eko Hari Purnomo dan Nur Aini Masruroh (Universitas Gadjah Mada, 2015)
Generally, there are two criteria which are widely used to determineDM’s weight of interest, i.e. competenceand consensus. Various studies related to determine DM’s weight of interest based on competence or consensusseparately have been conducted. Each criterion has its own advantages. The advantage of using competence as acriterion is DMs who have high competence based on their consistence on the decisions made will have high of interest weight. Meanwhile, consensus criterion emphasizes a DM/s contribution to a group without consideringthe DM’s ability or competence.Considering the advantages of both criteria, this study developed a model to determine DM’s weight of interestby considering the DM’ competence and consensus in a GDM. This study used2 group decision making cases totaling in 6 groups consisting of 5 people each. Collected data was then processedusing DM’s weight of interest determination method based on competence and consensus. A model was thendesigned using regression method and fuzzy method. Therefore, a model to determine DM’s weight of interest was obtained by considering competence and consensus. DM’s weight of interest from each method was then involvedin group decision making. The research result showed that group decisions made by involving DM’s weight of interest were better decisions. It implies competence and consensus are two criteria which can be used to determineDM’s weight of interest.